DETERMINAN MINAT NASABAH PENGGUNA JASA RAHN DAN IJARAH PADA KANTOR CABANG PEGADAIAN SYARIAH MADIUN - Amah, Nik (Universitas Muhammadiyah Surakarta, 2017)
This study aims to examine the determinants of customers interest who use rahn and ijarah services at the branch offices of Syariah Madiun branch covering the principles of syariah, ujrah, and service. Sampling was conducted by Accidental Sampling technique to get sample of 227 respondents. Data collection use questionnaires. The analysis method used in this research is Multiple Linear Regression Analysis. The result of the research shows that: (1) the application of sharia principle influences the customer interest who use rahn and ijarah service, (2) ujrah does not affect the customers interest who use rahn and ijarah services, (3) the service influences customers interest who use rahn and ijarah services, and (4) The application of sharia principles, ujrah, and services simultaneously affect the customers interest who use serve rahn and ijarah services.Â Keywords: syariah principle, ujrah, services, customer interest.